Did Covid-19 lockdown positively affect the urban environment and UN- Sustainable Development Goals? - Nigam, Ritwik (2022)
Nigam, R., Tripathi, G., Priya, T., Luis, A. J., Vaz, E., Kumar, S., Shakya, A., Damásio, B., Kotha, M., & Yu, B. (Ed.) (2022). Did Covid-19 lockdown positively affect the urban environment and UN- Sustainable Development Goals? PLoS ONE, 17(9), 1-21. [e0274621]. https://doi.org/10.1371/journal.pone.0274621